Enhanced aglycone production of fermented soybean products by Bacillus species - Dajanta, Katekan (Acta Biologica Szegediensis, 2009)
This study evaluated the effect of starter culture and fermentation period on the isoflavone content of protein-rich soybeans variety TG145. Initially, soybeans were washed, soaked in water for 16 h and autoclaved at 121°C for 40min. Three different bacterial starter cultures ( 104 CFU/g) namely Bacillus subtilis BEST195, B. subtilis Asaichiban and B. subtilis TN51 were then added and the fermentation was allowed to proceed at 42°C for 24 h (natto-style) and 72 h (thua nao-style). The quantities of six major isoflavones (daidzin, genistin, glycitin, daidzein, genistein, and glycitein) were then determined in these fermented soybean products using reverse phase HPLC technique. Generally, our results clearly showed that the content of total isoflavones in the fermented products prepared by Bacillus starter cultures greatly increased ranging from 43 to 99% compared to that of the unfermented autoclaved soybeans. In addition, a dramatic increase of aglycones was also observed (> 400%) in the soybean products fermented by Bacillus subtilis strain TN51. This present study suggests a promising use of Bacillus starter cultures in improving isoflavone compounds especially the aglycones which would benefit for novel functional food development.